2012
DOI: 10.1155/2012/469126
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis Assessment in Early-Stage Parkinson’s Disease: Comparing Parkinson’s Psychosis Questionnaire with the Brief Psychiatric Rating Scale in a Portuguese Sample

Abstract: Psychotic symptoms in Parkinson's disease (PD) are frequent, disabling, and an important prognostic factor. Thus, screening instruments for detecting psychosis in PD are needed. For this purpose, we applied the Parkinson's Psychosis Questionnaire (PPQ), a short structured questionnaire, which requires no specific training, along with the Brief Psychiatric Rating Scale, expanded version (BPRS-E), for rating general psychopathology, including psychotic symptoms. We evaluated, in a cross-sectional study, a Portu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Presence of positive symptoms varied across different assessment tools, most likely attributed to inconsistencies in criteria adopted by the scale. 24 As shown in Figure 1, the clinician detected the presence of hallucinations in patients who neither the patients nor their informants had reported. Based on their PDQ-39 scores, this group of patients had a poorer perceived quality of life compared to the rest of the sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of positive symptoms varied across different assessment tools, most likely attributed to inconsistencies in criteria adopted by the scale. 24 As shown in Figure 1, the clinician detected the presence of hallucinations in patients who neither the patients nor their informants had reported. Based on their PDQ-39 scores, this group of patients had a poorer perceived quality of life compared to the rest of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found differences in reported prevalence rates of hallucinations and psychosis in a large cohort of PD patients. Presence of positive symptoms varied across different assessment tools, most likely attributed to inconsistencies in criteria adopted by the scale . As shown in Figure , the clinician detected the presence of hallucinations in patients who neither the patients nor their informants had reported.…”
Section: Discussionmentioning
confidence: 99%
“…Common variations in study design identified from a targeted literature review (unpublished findings) include the criteria for patient selection, the definition of PDP, the symptoms of psychosis that were of interest to study investigators, differences in the methodology used to assess symptoms, and the timeframe over which symptoms were observed. For example, several studies have reported that inclusion of minor phenomena increases the observed prevalence rate of psychosis symptoms among patients with PD [47][48][49] and that standard assessment tools for PD symptomology, such as the thought disturbance item on the Unified Parkinson Disease Rating Scale (UPDRS) Part I have low sensitivity for capturing such phenomena. 50,51 The prevalence rates in the current study were estimated based on survey data reported retrospectively by medical practitioners.…”
Section: Disruptiveness and Comorbidity Ratesmentioning
confidence: 99%
“…[ 8 ] Therefore, the present study was undertaken to study the clinical profile of the patients with Parkinson's disease and psychosis using the neuropsychiatric inventory (NPI) for rating of psychotic symptoms. Although various scales have been used to assess psychosis in PD,[ 9 10 11 ] the NPI is a well-validated scale to screen for various psychotic symptoms in PD. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%